The effect of lime leaf extract (Citrus aurantifolia) through drinking water on the chemical and physical quality of broiler meat - Anantaputra, Ahmad Ghofari Ali (Institute for Advanced Science, Social, and Sustainable Future, 2023)
This study aims to investigate the impact of supplementing lime leaf extract (EDJ) in broiler chickens' drinking water on both the chemical and physical qualities of their meat. A total of 128 New Lohmann MB 202 strain broiler roosters were subjected to the same basal feed regimen but received distinct drinking water treatments over a 35-day rearing period. The drinking water treatments included plain water without additives (negative control; T0), water supplemented with 50 ppm Tetracycline antibiotics (positive control; T1), water enriched with 15 ml/liter EDJ (T2), and water infused with 30 ml/liter EDJ (T3). The basal diet consisted of corn and soybean flour, with a crude protein content of 22.01% and a metabolic energy level of 3113.12 kcal/kg. Feed and drinking water are provided ad libitum during the rearing period. The parameters observed in this study were the chemical and physical quality of the meat, which included variables: moisture content, ash content, protein content, fat content, pH value, water holding capacity, cooking loss, and tenderness. The data obtained were then analyzed for variance (ANOVA) using a one-way Complete Randomized Design based on a P value of less than 5%. The findings of the study indicated that the supplementation of EDJ through drinking water did not produce significant alterations in water content, protein content, fat content, cooking loss, or tenderness of the broiler meat. However, a notable outcome was observed: the addition of 30 ml/liter of EDJ to the drinking water led to a substantial increase in water holding capacity (P<0.05) while simultaneously reducing the meat's pH value (P<0.05). These results suggest that EDJ supplementation has the potential to enhance the physical quality of broiler meat, primarily by increasing water retention and decreasing pH values, which can contribute to improve meat texture and juiciness.